2013
DOI: 10.1097/pas.0b013e31828fc283
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Atypical Spitz Tumors With Chromosomal Copy Number Aberrations and Conventional Melanomas in Children

Abstract: Death due to melanoma in childhood (up to 20 y of age) is a rare event, with an average of 18 cases reported annually in the United States. In this study we evaluated 2 subgroups of high-risk melanocytic neoplasms in childhood, specifically atypical Spitz tumors (ASTs) with chromosomal copy number changes and conventional melanomas. We analyzed the clinical, histologic, and molecular features of all cases and performed the Fisher exact test, logistic regression, and multivariate analysis to evaluate features a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 31 publications
0
67
1
3
Order By: Relevance
“…Homozygous loss of CDKN2A by fluorescence in situ hybridization (FISH) is associated with more aggressive behavior in spitzoid tumors, whereas heterozygous loss is not diagnostic of malignancy [16][17][18][19]. Few studies have correlated p16 immunohistochemistry with CDKN2A copy number changes to assist diagnosticians in selecting FISH or immunohistochemistry as a diagnostic approach [16], and to our knowledge the correlation between p16 expression and CDKN2A copy number status in SMMs has not been systematically examined.…”
Section: Accepted Manuscriptmentioning
confidence: 89%
See 1 more Smart Citation
“…Homozygous loss of CDKN2A by fluorescence in situ hybridization (FISH) is associated with more aggressive behavior in spitzoid tumors, whereas heterozygous loss is not diagnostic of malignancy [16][17][18][19]. Few studies have correlated p16 immunohistochemistry with CDKN2A copy number changes to assist diagnosticians in selecting FISH or immunohistochemistry as a diagnostic approach [16], and to our knowledge the correlation between p16 expression and CDKN2A copy number status in SMMs has not been systematically examined.…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…An initial report found that 41% of SMMs harbor homozygous 9p21 deletion [17]. Further studies applied to spitzoid lesions classified as ASTs demonstrated that homozygous loss of 9p21 correlated with poor outcome, and may warrant classification of a tumor as malignant [16,18,19]. The significance of heterozygous CDKN2A loss in spitzoid neoplasms is less clear.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…Despite the above-mentioned data, [62][63][64]66 the prognostic impact of the new melanoma FISH probe cocktail in atypical Spitzoid tumors was recently questioned by Massi et al 68 ; these authors focused on lesions excised in patients younger than 18 years and found no significant correlation between the FISH status and the clinical outcome. Conventional 4-probe FISH was positive in 4/20 (20%) Spitz nevi and in 15/50 (30%) atypical Spitz tumors; in addition, 9p21 deletion was found as homozygous in 2 cases and as heterozygous in 3 cases of atypical Spitz tumor.…”
Section: Cautions About the New Melanoma Fish Testmentioning
confidence: 95%
“…17 Using fluorescence in situ hybridization methodology, loss of chromosome region 9P21 has been associated with aggressive behavior in a small subset of these lesions and represents, arguably, the best evidence-based genomic criterion for identification of lesions with potential competence for metastasis and lethal progression. 18,19 Comparative genomic hybridization methodology can identify similar abnormalities, 20 but has not been studied as rigorously in relation to outcome.…”
Section: Genomic Markersmentioning
confidence: 99%